2014
DOI: 10.1002/elps.201400080
|View full text |Cite
|
Sign up to set email alerts
|

Improving complex kinship analyses with additional STR loci

Abstract: In a standard paternity testing, mother, child, and alleged father are analyzed with STR markers using commercially available kits. Since Italian civil legislation does not have thresholds to confirm a paternity, paternity is practically proven when likelihood ratio increases prior probability of paternity to posterior, accepted by court as sufficient. However, in some cases the number of markers included in a commercial kit may be insufficient to conclusively prove or disprove a relationship between individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Studies suggest that genotyping more than 20 autosomal STR loci improve forensic personal identification, especially in the sibship analyses (Allen et al, 2007;Carboni et al, 2014;Von Wumb-Schwark et al, 2015;Tamura et al, 2015;Turrina et al, 2016), which corresponds to our findings.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Studies suggest that genotyping more than 20 autosomal STR loci improve forensic personal identification, especially in the sibship analyses (Allen et al, 2007;Carboni et al, 2014;Von Wumb-Schwark et al, 2015;Tamura et al, 2015;Turrina et al, 2016), which corresponds to our findings.…”
Section: Resultssupporting
confidence: 87%
“…The introduction of additional seven loci used in the PowerPlex ® Fusion System increased the values of LR in 5 out of 7 analyzed pairs. Carboni et al (2014) reported a case study of two women who were cousins and they suspected to be daughters of the same father. Their mothers were sisters and were not available for kinship testing.…”
Section: Resultsmentioning
confidence: 99%
“…However, supplementary STRs are required to significantly evaluate pairwise, distant and/or complex relationships [3][4][5]. Additionally, additional STRs may be needed to confirm paternity in cases in which genetic mutations occur between the parents and progeny [6], null alleles are present [7] or a relative of an alleged father is involved [8][9][10].…”
Section: Dear Editormentioning
confidence: 98%
“…Although X‐chromosomal, Y‐chromosomal STRs, or mtDNA can be helpful for kinship analysis, these markers only can be applied to particular cases and their discrimination powers are relative small owing to their unique genetic behaviors . Autosomal STR markers are necessary to solve the kinship problems . Additionally, linked autosomal markers are required to differentiate the second‐degree relationships (e.g.…”
Section: Discussionmentioning
confidence: 99%